Methionine plus cystine to lysine ratio in diets for tambatinga fingerlings - Costa,Dayana da Conceição da (2021)
ABSTRACT Among a variety of hybrids produced in Brazil, tambatinga is obtained from the crossing of a tambaqui female with a pirapitinga male. Although rapid weight gain in less time is an attractive characteristic from a commercial viewpoint, the information on its nutritional requirements, especially amino acid requirements, is limited. As corn and soybean meal-based diets available for fish contain deficient levels of essential amino acid methionine, our objective was to determine the digestible methionine plus cystine to lysine ratio in diets for tambatinga fingerlings. We used 900 fish with initial weights varying from 1.49 ±0.59 to 4.14 ±1.70 g, and they were fed six types of diets with different digestible methionine plus cystine to lysine ratios (50, 55, 60, 65, 70, and 75%). Performance parameters such as food efficiency, body depositions of protein, fat, and ash, and nitrogen retention efficiency were evaluated. The increase of digestible methionine plus cystine to lysine ratio in the diet improved quadraticly the feed intake, consumption of digestible methionine plus cystine, weight gain, specific growth rate and feed conversion, protein deposition and body ash and retention efficiency nitrogen until the estimated ratios of 57%, 73%, 58%, 58% and 59%, 59%, 58% and 60%, respectively; and reduced linearly the efficiency of using methionine plus cystine for the weight gain. On the other hand, body fat deposition was not affected. We concluded that the digestible methionine plus cystine: lysine ratio in the rations for tambatinga fingerlings is 59%, for provide better performance and body protein deposition.